Menyoal Kembali Teori Evolusi Agama J.G. Frazer dalam Keberagamaan Masyarakat Jawa - Muqtada, Muhammad Rikza (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
Religion is seen as the result of philosophersâ thinking production which has a tendencyÂ to solve the riddle of life and to spread their ideas and their thoughts to others. FrazerÂ is one pushed for discovering when the religion began to exist. The conclusion is thatÂ the human belief system, in accordance with a level of reasoning ability, evolves fromÂ magical belief, than religous belief, and ends on science. Nevertheless, when it isÂ compared to the religious phenomenon in Indonesia, especially in Java, Frazerâs theoryÂ is not entirely true and debatable. The religious system in Java exactly does not haveÂ evolution as interpreted in Frazerâs theory. With its elasticity, genuine Javanese beliefÂ â dynamism and animism â only underwent assimilation with foreign cultures thatÂ came later like Islam and Christian, and including Western culture. In the context ofÂ Javanese religiosity, those three beliefs system as intended by Frazer, take place integrallyÂ and parallel in modern Javanese culture.